Magneto-optical trap for neutral mercury atoms - 刘洪力 尹士奇 刘亢亢 钱军 徐震 洪涛 王育竹 (Chinese physics B, 2013)
Due to its low sensitivity to blackbody radiation, neutral mercury is a good candidate for the most accurate optical lattice clock. Here we report the observation of cold mercury atoms in a magneto-optical trap （MOT）. Because of the high vapor pressure at room temperature, the mercury source and the cold pump were cooled down to 40℃ and 70 ℃, respectively, to keep the science chamber in an ultra-high vacuum of 6×10^-9 Pa. Limited by the power of the UV cooling laser, the one beam folded MOT configuration was adopted, and 1.5×10^5 Hg-202 atoms were observed by fluorescence detection.